Investacte the Role of Weissella Confuse on TNF-α in Serum and Liver Tissue of Mice Infected with Leishmania Donovani - Dhilal Abdulelah Ibraheem (Journal of Global Pharma Technology, 2020)
Leishmaniasis is one,of the vector-borne diseases, caused by obligate protozoan parasites, they are.transmitted by sand, flies as extracellular. Flagellatedepromastigotes thatereplicate as an intracellulareparasite in.mononuclear cells of mammalian.hosts. Probiotics are microorganisms that provide health benefits when consumed and characterized by being of human origin, probiotics have benefits in health and diseases, there is some clinical applications using probiotic like: immunity function by increasing the number of IgA-producing plasma cells, improving phagocytosis as well as increasing the proportion of T lymphocytes and Natural Killer cells. The present study it is efficiency against Leishmania donovani compared with pentostam drug in vivo by measuring the levels of immune cytokines (TNF-α) in serum and liver tissue of infected mice and treatment with Weissella confuse bacteria and its supernatant for three weeks. The results of measuring the levels of TNF-α showed significant increase in mice serum and the concentration of TNF-α in liver tissue by immunohistochimsry showed increase in TNF-α secretion of treated mice with Weissella confuse bacteria and pentostam compared to non infected mice while mice treated with Weissella confuse supernatant showed less increase compared to the two previous groups. Probiotic bacteria and its supernatant have an affect on Leishmania donovani parasite through induce pro and anti-inflammatory cytokines in vivo. Keyword: Leishmania, Probiotic, TNF-α, Weissella confuse, Immunohistochimsry.